A Comparative Histomorphological Study of the Pancreas in the Chukar Partridge (Alectoris chukar )and Moorhen Bird (Gallinula chloropus) - Ibrahim, Raad Shaalan (Diyala Journal for Veterinary Sciences, 2024)
The objective of this study was to conduct a comparative analysis of the structural and histological characteristics of the pancreas in Chukar Partridges and Moorhen birds. The focus of this study was to assess the worth of these avian species in terms of their potential as viable sources for meat and egg production. The avian specimens were categorized into two distinct groups: one designated for anatomical examination, while the other was allocated for histological analysis. The pancreas in Chukar Partridge was characterized by its white, pinkish coloration and weighs around 0.880± 0.67 g. It is 8.3±1.35 cm in length and 1.3± 0.56 cm in width. The pancreas of common moorhen birds was characterized by its white to pinkish coloration. It weighs around 0.994± 0.89 g, has a length of 9.1± 1.93 cm, and a width of 1.5± 0.84 cm. From a histological perspective, it appears that the connective tissue capsule was comparatively thinner in the Chukar partridge as compared to the Moorhen bird. The connective tissue capsule spans from the septa to the parenchyma of the pancreas, exhibiting a lower abundance in the Chukar partridge compared to the moorhen bird. Serous tubulo-acinar glands were present in the exocrine glands of both birds. The acinar cells of the Chukar partridge’s secretory acini had a pyramidal morphology. The secretory acini of the moorhen bird was characterized by the presence of acinar cells that have an oval, elongated form. The morphology of the islets exhibited irregular or elongated shapes in Chukar Partridge, whereas in Moorhen Bird, they appeared as oval or uneven structures. The Chukar partridge showed a greater abundance of endocrine cells compared to the Moorhen bird, as evidenced by the higher density of small blood arteries inside these cells.